Smart Heart Band; The Development of Effective Emergency Band - Yusuf, Nurul Iman; Sinnathamudhu, Jasshween Godha; Mahalinga Moorthy, Jaysrini; Shelena Soosay Nathan (Multidisciplinary Applied Research and Innovation, 2022)
Heart disease is quite common among the elderly and statistics show that the risk of heart disease increases greatly as they age. Besides that, older people are also novice users of smart technologies and thus lead them to be underutilizing it during emergencies especially. This study provides a simple smart solution that integrates Internet of Things (IoT) named Smart Heart Band for people with heart disease and also targeting those with heart issues in contacting closed ones during emergencies. This smart band aims to be able to assist the elderly to notify their closed ones during emergencies and to curb the issues of unnoticed death or sudden attacks. The study uses input, process, output methods in the development of this tool and through the use of hardware such as NodeMCU, pulse sensor, buzzer and button. Alongside with it, software like Blynk were used in notifying the emergency contact in time of need. Testing shows that the user finds the smart band as a useful thing in time of emergency and would be able to notify needed people during an emergency. In conclusion, it is proven that the smart band is able to help reduce the risk of sudden death among the elders due to heart attack problems and enable them to reach the needed people in time to get medical attention as soon as possible. In future, the smart band can be connected with medical personnel to be attended immediately and have accurate diagnosis.